P2X7 Nucleotide and EGF Receptors Exert Dual Modulation of the Dual-Specificity Phosphatase 6 (MKP-3) in Granule Neurons and Astrocytes, Contributing to Negative Feedback on ERK Signaling - Queipo, Mª José; Gil-Redondo, Juan C.; Morente, Verónica; Ortega, Felipe; Miras-Portugal, Mª Teresa; Delicado, Esmerilda G.; Pérez-Sen, Raquel (Frontiers in Molecular Neuroscience, 2018)
Extracellular signal-regulated kinases 1 and 2 (ERK1/2) play a central role in the intracellular signaling of P2X7 nucleotide receptors in neurons and glial cells. Fine spatio-temporal tuning of mitogen-activated protein (MAP) kinases is essential to regulate their biological activity. MAP kinase phosphatases (MKPs) are dual specificity protein phosphatases (DUSPs) that dephosphorylate phosphothreonine and phosphotyrosine residues in MAP kinases. This study focuses on how DUSP, DUSP6/MKP3, a phosphatase specific for ERK1/2 is regulated by the P2X7 nucleotide receptor in cerebellar granule neurons and astrocytes. Stimulation with the specific P2X7 agonist, BzATP, or EGF (positive control for ERK activation) regulates the levels of DUSP6 in a time dependent manner. Both agonists promote a decline in DUSP6 protein, reaching minimal levels after 30 min yet recovering to basal levels after 1 hour. The initial loss of protein occurs through proteasomal degradation, as confirmed in experiments with the proteasome inhibitor, MG-132. Studies carried out with Actinomycin D demonstrated that the enhanced transcription of the Dusp6 gene is responsible for recovering the DUSP6 protein levels. Interestingly, ERK1/2 proteins are involved in the biphasic regulation of the protein phosphatase, being required for both the degradation and the recovery phase. We show that direct Ser197 phosphorylation of DUSP6 by ERK1/2 proteins could be part of the mechanism regulating their cytosolic levels, at least in glial cells. Thus, the ERK1/2 activated by P2X7 receptors exerts positive feedback on these kinase’s own activity, promoting the degradation of one of their major inactivators in the cytosolic compartment, DUSP6, both in granule neurons and astrocytes. This feedback loop seems to function as a common universal mechanism to regulate ERK signaling in neural and non-neural cells.